2017
DOI: 10.1158/1055-9965.epi-17-0246
|View full text |Cite
|
Sign up to set email alerts
|

The Premenopausal Breast Cancer Collaboration: A Pooling Project of Studies Participating in the National Cancer Institute Cohort Consortium

Abstract: Breast cancer is a leading cancer diagnosis among premenopausal women around the world. Unlike rates in postmenopausal women, incidence rates of advanced breast cancer have increased in recent decades for premenopausal women. Progress in identifying contributors to breast cancer risk among premenopausal women has been constrained by the limited numbers of premenopausal breast cancer cases in individual studies and resulting low statistical power to subcategorize exposures or to study specific subtypes. The Pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 106 publications
1
20
0
Order By: Relevance
“…Our case-control analysis revealed that patients with a BMI of 30 kg/m 2 or more had more chance for getting disease compared with patients with a BMI below 29 kg/m 2 (p < 0.001). Our findings in this regard are in line with the results of former research in other countries [22] [23] [24]. Moreover, there is no evidence that the assumption of a simple linear or a log-linear relationship between BMI and BC risk is real, in particular when BMI is less than 25 kg/m 2 [25].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our case-control analysis revealed that patients with a BMI of 30 kg/m 2 or more had more chance for getting disease compared with patients with a BMI below 29 kg/m 2 (p < 0.001). Our findings in this regard are in line with the results of former research in other countries [22] [23] [24]. Moreover, there is no evidence that the assumption of a simple linear or a log-linear relationship between BMI and BC risk is real, in particular when BMI is less than 25 kg/m 2 [25].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, there is no evidence that the assumption of a simple linear or a log-linear relationship between BMI and BC risk is real, in particular when BMI is less than 25 kg/m 2 [25]. The mechanisms underlying the relationship between high BMI and BC in women was discussed in the literature and it was primarily the result of the associated increase in estrogens, particularly bioavailable estradiol [22] [26].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, our results are based on the largest study of prospective data to date and contribute to the accumulating evidence that etiological heterogeneity exists in breast carcinogenesis. Pooled analyses of studies with more detailed exposure and tumor classification are likely to be increasingly informative about etiology and risk factor identification (37). More precise estimates of risk factor associations will be required to improve risk assessment models with clinicopathological data.…”
Section: Discussionmentioning
confidence: 99%
“…The small number of breast cancer cases and births that occurred at same integer age ( N = 39) resulted in wide CIs for the HR estimate for the first year after childbirth. Our analyses do not address breast cancer risk after age 55 years because of limits of the data provided to the Premenopausal Breast Cancer Collaborative Group (20). We did not address associations according to intervals between births; 1 prior study has suggested that longer intervals could magnify childbirth-related increases in breast cancer risk (17).…”
Section: Discussionmentioning
confidence: 99%
“…We used data from the Premenopausal Breast Cancer Collaborative Group, a pooling project involving 20 prospective cohort studies (20). This work was approved by the relevant institutional review boards.…”
Section: Methodsmentioning
confidence: 99%